E-Commerce as a Source of Cyber Crime - Reda Manthovani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2019)
E-commerce is a type of electronic business mechanism that focuses on individual-based business transactions using the internet (digital network-based technology) as a medium for exchanging goods or services between two institutions (B to B) and institutions to direct consumers (B to C). The aim of this research is the effectiveness and efficiency of electronic transaction law in Indonesia. The research method used is normative juridical with a statutory approach using primary and secondary legal sources, the results show that crimes committed through online networks are either online auction fraud, check fraud, credit card fraud, trust fraud, identity fraud, pornography. children, and others cannot be dealt with firmly so that these actions can damage the business climate. So it could be said that our legal system has not been effective in preventing cyber crime.